Chemical‐Driven Outflow of Dissociated Amyloid Burden from Brain to Blood. Issue 12 (2nd February 2022) - Lee, Donghee; Kim, Hyunjin Vincent; Kim, Hye Yun; Kim, YoungSoo
Abstract: Amyloid‐β (Aβ) deposition in the brain is a primary biomarker of Alzheimer's disease (AD) and Aβ measurement for AD diagnosis mostly depends on brain imaging and cerebrospinal fluid analyses. Blood Aβ can become a reliable surrogate biomarker if issues of low concentration for conventional laboratory instruments and uncertain correlation with brain Aβ are solved. Here, brain‐to‐blood efflux of Aβ is stimulated in AD transgenic mice by orally administrating a chemical that dissociates amyloid plaques and observing the subsequent increase of blood Aβ concentration. 5XFAD transgenic and wild‐type mice of varying ages and genders are prepared, and blood samples of each mouse are collected six times for 12 weeks; three weeks of no treatment and additional nine weeks of daily oral administration, ad libitum, of Aβ plaque‐dissociating chemical agent. By the dissociation of Aβ aggregates, the altered levels of plasma Aβ distinguish between transgenic and wild‐type mice, displaying potential as an amyloid burden marker of AD brains. Abstract : Blood amyloid‐β (Aβ) can become a reliable surrogate biomarker if the issue of low concentration can be overcome. The brain‐to‐blood efflux driven by the oral administration of an Aβ disaggregator dissolves plaques and subsequently increases the plasma Aβ levels. This result reflects the brain amyloid burden and distinguishes Alzheimer transgenic mice and non‐Alzheimer mice.